Impact of Covid-19 on Nursing Labor Safety in Chile: A Post-Pandemic Study; Impacto del Covid-19 en la Seguridad Laboral de Enfermería en Chile: Un Estudio Post Pandemia - Pavez-Lizarraga, A (Escuela de Enfermeria Pontificia Universidad Catolica de Chile, 2025)
The COVID-19 pandemic had a profound impact on healthcare professionals, particularly nursing staff, who were exposed to demanding working conditions and a heavy emotional burden. OBJECTIVE. To describe the perception of working conditions, job security, and their relationship with sociodemographic variables among nurses during the post-COVID-19 pandemic stage. METHODOLOGY. A cross-sectional study with an associative design was conducted with a sample of 124 nurses. Data were collected using validated instruments, and statistical analysis included measures of central tendency, dispersion, and frequencies. The variance ratio test was used to assess homogeneity of variance, and the Shapiro-Wilk test was applied to assess normality. The non-parametric Kruskal-Wallis test was used to compare scale scores by sex, marital status, and contract type. A p-value < 0.05 was considered statistically significant. The study was approved by the scientific ethics committee. DISCUSSION. The results reveal a work experience marked by uncertainty and exhaustion, consistent with previous studies on the psychosocial impact of the pandemic. Strengths such as resilience and teamwork were identified, alongside persistent structural gaps that affect job stability and emotional well-being. CONCLUSION. It is essential to advance policies that promote better structural conditions, professional recognition, and psychosocial support strategies for nursing personnel in post-crisis contexts. © 2025, Escuela de Enfermeria Pontificia Universidad Catolica de Chile. All rights reserved.